Tracheostomy in COVID-19: A retrospective cohort study of outcomes and mortality predictors in a specialized infectious disease hospital in Brazil - André Figueiredo Accetta; Denise Machado Medeiros; Maria Pia Diniz Ribeiro; Sandra Wagner Cardoso; Isabel Cristina Ferreira Tavares; Valdilea Gonçalves Veloso; Hugo Boechat Andrade; André Miguel Japiassú (PLoS ONE, 2025)
Background The COVID-19 pandemic profoundly impacted critical care practices, leading to a significantly increase in tracheostomies for patients with respiratory failure. This study aimed to investigate prognostic factors associated with mortality in COVID-19 patients undergoing tracheostomy for respiratory failure in the intensive care unit of a specialized infectious disease hospital in Brazil. Research Question What is the impact of the timing of tracheostomy on the outcome of COVID-19 patients?. Materials and methods This retrospective cohort study analyzed 356 COVID-19 patients who underwent tracheostomy at the Evandro Chagas National Institute of Infectious Diseases (INI) in Brazil between May 2020 and December 2023. Data on demographics, comorbidities, illness severity, surgical factors, and outcomes were extracted from medical records. Multivariate logistic regression was performed to identify factors associated with hospital mortality. Results The overall hospital mortality rate was 68%. Independent factors associated with mortality included age over 60 years, chronic pulmonary disease, diabetes, lack of COVID-19 vaccination, hemodialysis on the day of surgery, and a PaO2/FiO2 ratio lower than 200 on the day of surgery. The timing of tracheostomy (after 21 days of mechanical ventilation) was not associated with mortality. Conclusions This study offers valuable insights into the complex factors influencing mortality in critically ill COVID-19 patients. Our findings underscore the importance of assessing both patient characteristics and illness at the time of tracheostomy to predict outcomes which is more critical than basing the decision solely on the duration of endotracheal intubation or mechanical ventilation.